Response to Hong and Luparello (2024) - Orr, Scott,Hong, Joonkyo,Luparello, Davide (Institute for Replication, 2024)
I would like to thank Hong and Luparello (2024) for their effort in replicating, as well as partially extending, the results in Orr (2022). This replication report makes what I believe to be three key points: 1. The replication package of Orr (2022) is computationally reproducible (up to two minor caveats, which I very much appreciate the authors catching) 2. The demand estimates are sensitive to a 30% cost-share threshold pursued when con- structing input price based IVs. 3. The demand estimation strategy does not work when applied to a different sample (the same industry, but a later time period). - In this brief note, I provide some minor commentary on each of these findings. I focus primarily on point 2, where my interpretation of their results differs slightly from their own. In particular, I believe these results largely show that the cost-share threshold does not matter much quantitatively | as long one is careful to choose thresholds that make economic sense | although I also acknowledge that the precision of the estimates can be sensitive to this threshold.
10419/305230
Keywords: Graue Literatur; Produktionsfaktor; Allokation; Produktivität; Mehrproduktfertigung; Maschinenbau; Replikationsstudie; Indien